The Spectres of Schmitt: Identity, Decision, and the Name of YHWH - Pittl, Sebastian (Louvain studies, 2019)
This article investigates the legacy of the 'political theology' of the German legal scholar Carl Schmitt (1888-1985) in the oeuvres of the French philosopher Alain de Benoist (°1943), intellectual key figure of Europe's 'New Right', and the political philosopher Chantal Mouffe (°1943), one of the most prominent thinkers of a Schmitt-inspired left, and critically analyses the compatibility of a radical decisionism (as defended by Benoist, Mouffe and Schmitt) with a Christian perspective. A first part examines Schmitt's influence on the ideological cornerstones of the 'New Right' and the ways in which they are entangled with illiberal religious options, ultimately grounded in a form of radical decisionism. A second part contrasts Benoist's reading of Schmitt with the reception of Schmitt's thinking in the work of Mouffe. It is argued that due to sharing Schmitt's decisionism, Mouffe's attempt to think both 'with and against Schmitt' ultimately suffers from similar aporias as does Benoist's reading of Schmitt and thus fails to offer a viable democratic alternative. The last part of the article turns back to Schmitt himself to analyse whether a radical decisionist position is compatible with Judeo-Christian tradition. It critically examines Schmitt's references to papal infallibility as an alleged role model of decisionist sovereignty and investigates different theological concepts of divine sovereignty, which at first sight seem to invite a decisionist reading. Taking the revelation of God's name in Ex. 3:14 as central point of reference, an understanding of Judeo-Christian identity is then developed that is neither essentialist nor decisionist and thus offers a promising perspective from which to criticize the attempts to monopolize the Christian tradition by current proponents of the 'New Right'.